2012
DOI: 10.1021/la301764t
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Phases of Nanoparticle Langmuir Films

Abstract: We report on an in-situ observation of the colloidal silver nanoparticle self-assembly into a close-packed monolayer at the air/water interface followed by a 2D to 3D transition. Using the fast tracking GISAXS technique, we were able to observe the immediate response to the compression of the self-assembled nanoparticle layer at the air/water interface and to identify all relevant intermediate stages including those far from the equilibrium. In particular, a new nonequilibrium phase before the monolayer collap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
3
34
0
Order By: Relevance
“…Therefore, the particles are at short distances ordered in the same way as in sample A. Similar behavior has been observed for Langmuir films of silver NP at variable area, where for low particle densities the mean inter-particle distance remained unchanged [15].…”
Section: Experimental 21 Sample Preparationsupporting
confidence: 79%
“…Therefore, the particles are at short distances ordered in the same way as in sample A. Similar behavior has been observed for Langmuir films of silver NP at variable area, where for low particle densities the mean inter-particle distance remained unchanged [15].…”
Section: Experimental 21 Sample Preparationsupporting
confidence: 79%
“…To normalize for trough area, the isotherms are plotted in terms of ! vs surface mass density of sample.Previous X-ray and TEM experiments[3][4][5][6] indicate the pressure regimes in which the different nanoparticle films remain in the monolayer phase. We focus on comparing the compressive and shear moduli of our nanoparticle and lipid films in these regions, which are indicative of monolayer Langmuir films.Lipid Films.…”
mentioning
confidence: 98%
“…Like amphiphilic molecules, these capped nanoparticles self-assemble into 2D lattices at the air-water interface. [3][4][5][6][7][8][9][10][11][12][13][14] Nanoparticles exhibit remarkable physical properties including quantum confinement, 15 plasmon resonance 9,[16][17][18][19] and superparamagnetism 5,20 Thin films composed of nanoparticles have shown potential applications in biosensors 16,19,21 , high sensitivity resonators 14 , filtration devices 22 , magnetoresistive devices 10 , and flexible electronics. [23][24][25] Langmuir monolayers in particular have remarkable mechanical properties as two-dimensional materials that can extend into the third dimension.…”
mentioning
confidence: 99%
“…Formation of bilayer structures was reported as well for gold [23] and silver [24] nanoparticles. A study on the formation of Ag nanoparticle film using X-ray grazing incidence small angle scattering, Brewster angle microscopy and imaging ellipsometry was published recently [25,26]. It was observed that a nanoparticle monolayer is formed via coalescence of free self-assembled nanoparticle islands with a hexagonal closepacked order at the early stage of compression.…”
Section: Introductionmentioning
confidence: 99%